Repercussões socioambientais da atuação do Ministério Público da Paraíba na garantia da adequada destinação dos resíduos sólidos urbanos: uma análise do programa "Fim dos lixões" - Figueiredo Neto, Luis Nicomedes de (My University, 2025)
This dissertation aims to analyze the extrajudicial actions of the Public Prosecutor's Office of Paraíba (MPPB, acronym in Portuguese) in the eradication of open-air dumps between 2018 and 2024, with emphasis on the socio-environmental repercussions for waste pickers, based on the implementation of the "End of Dumps" program. The improper management of municipal solid waste, particularly through the persistence of open-air dumps, constitutes one of Brazil's most significant socio-environmental challenges. In Paraíba, by 2018, only 29 out of 223 municipalities ensured environmentally appropriate final disposal of solid waste. In response, the MPPB, in coordination with other institutions such as the Federal Public Prosecutor's Office (MPF, acronym in Portuguese), the Superintendence of Environmental Administration (SUDEMA, acronym in Portuguese), the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA, acronym in Portuguese), and the Federation of the Municipalities of Paraíba (FAMUP, acronym in Portuguese), developed the "End of Dumps" program. This initiative aimed at the progressive eradication of such areas and compliance with the guidelines established by Law nº 12.305/2010 (PNRS, acronym in Portuguese). The legal and socio-environmental issue examined concerns violations of environmental regulations and the social consequences of dump closures, particularly for recyclable waste pickers. Although essential for environmental preservation and public health, the closure of these sites demands public policies capable of fostering the productive and social reintegration of affected workers. The relevance of this study lies in the need to understand, from both legal and social perspectives, the effects of the Public Prosecutor's role in consolidating the PNRS, in light of the fundamental right to an ecologically balanced environment and the principles of human dignity and socio-environmental justice. The research adopted the deductive method, with a predominantly qualitative and, to a lesser extent, quantitative approach. It is exploratory and descriptive in nature, relying on a literature review and documentary analysis, especially of technical data and reports issued by the MPPB. The findings indicate significant progress in the proper disposal of solid waste in Paraíba, culminating in the closure of all open-air dumps by the end of 2024. However, it became evident that greater attention must be given to the social inclusion of waste pickers, whose livelihoods were directly affected by the elimination of informal workspaces. Although the MPPB acted strategically and in coordination with other institutions, the effectiveness of environmental protection depends on integrated measures of social justice, especially the inclusion of waste pickers in formal selective collection programs. It is concluded that the MPPB's actions were essential for implementing the PNRS, particularly through the use of extrajudicial instruments such as Non-Prosecution Agreements (ANPPs, acronym in Portuguese) and Conduct Adjustment Terms (TACs, acronym in Portuguese). Nevertheless, to ensure the effectiveness of public policies and the full protection of socio-environmental rights, it is crucial to integrate waste pickers into recycling production chains, ensuring them citizenship, decent work, and social recognition. [resumo fornecido pelo autor]
A presente dissertação tem como objetivo geral analisar a atuação extrajudicial do MPPB na erradicação dos lixões entre 2018 e 2024, com ênfase nas repercussões socioambientais para os catadores de resíduos, a partir da execução do programa "Fim dos Lixões". A gestão inadequada dos resíduos sólidos urbanos, especialmente pela permanência de lixões a céu aberto, configura um dos mais relevantes problemas socioambientais do Brasil. Na Paraíba, em 2018, apenas 29 dos 223 municípios realizavam a destinação final ambientalmente adequada dos resíduos sólidos urbanos. Diante desse cenário, o Ministério Público da Paraíba (MPPB), inicialmente, em articulação com outras instituições, como o Ministério Público Federal, a Superintendência da Administração do Meio Ambiente (SUDEMA), o Instituto Brasileiro do Meio Ambiente e dos Recursos Renováveis (IBAMA) e a Federação das Associações de Municípios da Paraíba (FAMUP), desenvolveu o programa "Fim dos Lixões". A iniciativa visou à erradicação progressiva dessas áreas e ao cumprimento das diretrizes da Lei nº 12.305/2010 (Política Nacional de Resíduos Sólidos ? PNRS). O problema jurídico e socioambiental examinado envolve a violação das normas ambientais e as consequências sociais da desativação dos lixões, especialmente para os catadores de materiais recicláveis. Embora essencial para a preservação ambiental e da saúde pública, o encerramento desses espaços exige políticas públicas capazes de promover a reinserção produtiva e social dos trabalhadores impactados. A relevância do tema reside na necessidade de compreender, sob os enfoques jurídico e social, os efeitos da atuação do Ministério Público na consolidação da PNRS, à luz do direito fundamental ao meio ambiente ecologicamente equilibrado e dos princípios da dignidade da pessoa humana e da justiça socioambiental. Adotou-se o método dedutivo, com abordagem predominantemente qualitativa e, em menor grau, quantitativa. A investigação foi de natureza exploratória e descritiva, valendo-se de revisão bibliográfica e análise documental, especialmente de dados e relatórios técnicos do MPPB. Os resultados apontam avanços significativos na destinação adequada dos resíduos sólidos na Paraíba, culminando no encerramento de todos os lixões no final do ano de 2024. Contudo, verificou-se a necessidade de maior atenção à inclusão social dos catadores, cuja atividade foi diretamente afetada pela extinção dos espaços informais de trabalho. Embora o MPPB tenha atuado de forma estratégica e articulada, constatou-se que a efetividade da proteção ambiental exige medidas integradas de justiça social, especialmente a valorização dos catadores por meio de sua inserção em programas formais de coleta seletiva. Conclui-se que a atuação do MPPB foi essencial para a implementação da PNRS, destacando-se pelo uso de instrumentos extrajudiciais, como os Acordos de Não Persecução Penal (ANPPs) e os Termos de Ajustamento de Conduta (TACs). Entretanto, para garantir a efetividade das políticas públicas e a proteção integral dos direitos socioambientais, é imprescindível inserir os catadores nas cadeias produtivas da reciclagem, assegurando-lhes cidadania, trabalho decente e reconhecimento social. [resumo fornecido pelo autor]
Keywords: Direito ambiental; Meio ambiente; Gerenciamento de resíduos - Paraíba; Paraíba. Ministério Público; Lixo - Eliminação - Aspectos ambientais; Catadores de lixo; Environmental law; Environment; Waste management - Paraíba (Brazil); Paraíba(Brazil). Public Ministry; Refuse and refuse disposal - Environmental aspects; Ragpickers